Noise-Robust Online Measurement of the On-State Resistance of the Power Semiconductor Devices in PWM Converters - Junho Shin; Jong-Won Shin; Wonhee Kim (IEEE Access, 2024)
The increase in ${R} _{DUT}$ , the on-state resistance of power semiconductor devices, is used to estimate the remaining useful life (RUL) of the devices. Conventional online measurement of $R_{DUT}$ involves on-state voltage measurement of the on-state device, which is easily polluted by switching noise to limit the measurement accuracy. This paper proposes a new noise-robust method to measure the increment of $R_{DUT}$ by inductor current and input/output DC voltage of DC-DC converters. The proposed method features higher accuracy in predicting RUL than the conventional one because the inductor current is immune to switching noise. The aging of MOSFET is emulated in this paper by adding a series resistor $R_{ext}$ . Experiments showed that the resistance increment measured by the proposed method is up to 99.2% accurate to value of $R_{ext}$ .